The Impact of Emotional Regulation Training on Enhancing Emotion Management Competencies in Students - Dwidiyanti, Meidiana; Wijayanti, Diyan Yuli; Santoso, Agus; Hartati, Elis; Dewi, Nur Setiawati; Andriany, Megah; Ulliya, Sarah; Hikmat, Rohman (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Disturbed mental health among students had a very strong negative impact on physical health, interpersonal communication, and academic ability. Mental health issues in students were caused by pent-up emotions or traumatic events they had experienced. At that time, there was no specific intervention on campus aimed at preventing mental disorders among students. As a result, many emotional problems went unaddressed, increasing the risk of mental disorders among students. The purpose of this study was to improve students' emotional management through emotional regulation training. This study was a quantitative research with a quasi-experimental design using a one-group pre-post-test approach. The respondents of this study were 100 nursing students. The instruments used included an emotional regulation questionnaire and an independent healthy achievement checklist that had been tested for validity and reliability. The data normality test was conducted using the Kolmogorov-Smirnov test, and data analysis was performed using the Wilcoxon test. The results of this study indicated a p value 0.05, demonstrating a significant difference in emotional regulation and emotional management before and after the emotional regulation training was administered. The conclusion of this study was that emotional regulation training was an appropriate intervention to address emotional problems, help improve emotional management skills, and prevent the risk of mental health disorders among students on campus.